Trends in the Development of World Trade before and after the Global Financial and Economic Crisis - Gostomski, Eugeniusz; Michałowski, Tomasz (Studia Oeconomica Posnaniensia, 2017)
The subject of discussion in this paper are the changes which have taken place in world trade since 1950. The authors analyse changes in the value, volume, as well as commodity and geographical structure of trade. Particular attention is devoted to the period of the global financial and economic crisis, when the largest contraction in global trade since the end of World War II was observed. In the end, the most important focus in on prospects for the further development of global trade. The paper has been based on the available literature on the subject, reports of international organizations and statistics.